Seawater gel in allergic rhinitis: Entrapment effect and mucociliary clearance compared with saline - Cingi, Cemal; Halis Unlu, H.; Songu, Murat; Yalcin, Sinasi; Topcu, Ismail; Cakli, Hamdi; Bal, Cengiz (My University, 2010)
Objective: We performed a prospective study to investigate the the efficacy of seawater gel in reducing symptoms in patients with mild allergic rhinitis. We also aimed to investigate the impact of nasal irrigation on mucociliary clearance with seawater gel compared with saline in this patient group. Methods: The study was performed in 100 consecutive adult individuals with a history of allergic rhinitis that was not controlled by anti-allergic drugs. Patients were assigned to receive seawater gel nasal spray for 10 days. The efficacy of treatment was assessed by means of total nasal symptom score and clinical findings. Results: A statistically significant difference was found between scores of ‘nasal discharge, nasal obstruction, sneezing, nasal itching—before and after treatment (p < 0.001). Clinical findings evaluation revealed a statistically significant decrease in lower turbinate colour rating and turbinate congestion at the end of treatment (p< 0.001). Saccharin transit time decreased from baseline in the seawater trials by 12% compared with a 4% decrease for saline. The difference between the percent changes was statistically significant (t = 2.177; p < 0.05). Conclusions: The present study provides evidence that a four times daily regimen of seawater gel can be an adjunctive therapy in the patient with allergic rhinitis. © 2010, SAGE Publications. All rights reserved.
Keywords: allergen; allergic rhinitis; entrapping; nasal lavage; nasal rinsing; seawater